Inhibition of jasmonate-mediated plant defences by the fungal metabolite higginsianin B. (1st February 2020) - Dallery, Jean-Félix; Zimmer, Marlene; Halder, Vivek; Suliman, Mohamed; Pigné, Sandrine; Le Goff, Géraldine; Gianniou, Despoina D; Trougakos, Ioannis P; Ouazzani, Jamal; Gasperini, Debora; O'Connell, Richard J
Abstract: Infection of Arabidopsis thaliana by the ascomycete fungus Colletotrichum higginsianum is characterized by an early symptomless biotrophic phase followed by a destructive necrotrophic phase. The fungal genome contains 77 secondary metabolism-related biosynthetic gene clusters, whose expression during the infection process is tightly regulated. Deleting CclA, a chromatin regulator involved in the repression of some biosynthetic gene clusters through H3K4 trimethylation, allowed overproduction of three families of terpenoids and isolation of 12 different molecules. These natural products were tested in combination with methyl jasmonate, an elicitor of jasmonate responses, for their capacity to alter defence gene induction in Arabidopsis. Higginsianin B inhibited methyl jasmonate-triggered expression of the defence reporter VSP1p:GUS, suggesting it may block bioactive jasmonoyl isoleucine (JA-Ile) synthesis or signalling in planta . Using the JA-Ile sensor Jas9-VENUS, we found that higginsianin B, but not three other structurally related molecules, suppressed JA-Ile signalling by preventing the degradation of JAZ proteins, the repressors of jasmonate responses. Higginsianin B likely blocks the 26S proteasome-dependent degradation of JAZ proteins because it inhibited chymotrypsin- and caspase-like protease activities. The inhibition of target degradation by higginsianin B also extended to auxin signalling, as higginsianin B treatment reduced auxin-dependent expression of DR5p:GUS . Overall, our data indicate that specific fungal secondary metabolites can act similarly to protein effectors to subvert plant immune and developmental responses. Abstract : A diterpene secondary metabolite produced by a fungal pathogen suppresses plant jasmonate defence signalling by preventing the proteasomal degradation of JAZ repressor proteins.